Micropropagation of Erodium sibthorpianum subsp sibthorpianum, an endemic threatened species of Uludag Mountain (Bursa-Turkey) - Akin, Betul; Kocacaliskan, Ismail; Guleryuz, Gurcan (Tubitak Scientific & Technological Research Council Turkey, 2014)
Uludag Mountain is one of the Important Plant Areas of Turkey. Its native plant species are threatened by various human and environmental factors. In this study, 2 different micropropagation techniques, with Murashige Skoog (MS) and modified MS (ModMS) media, were used for Erodium sibthorpianum Boiss. subsp. sibthorpianum. Mineral composition was developed according to the plant requirements. Shoot tips were cultured on these media. Seedlings, obtained from in vitro germinated seeds, were used as explant sources in micropropagation studies. The highest percentage of shoot induction (11.33 shoots/explant) was determined in 1 ppm 6-benzyl amino purine and plant growth regulator-free MS medium (35.97 mm shoot length). Elongated shoots were successfully rooted in the ModMS medium with different naphthalene acetic acid concentrations. Shoots with regenerated roots were transferred to the greenhouse. This protocol could be used for conservation studies of endemic and endangered plant species.
Keywords: Erodium sibthorpianum; endangered; endemic; micropropagation; IN-VITRO PROPAGATION; PLANT-REGENERATION; RARE; CONSERVATION; CULTURE; L.; CALLUS; Plant Sciences